International relations between Britain and America, 1796-1848. - Vaughan, Charles Richard, 1774-1849; Liston, Robert, Sir, 1742-1836; All Souls College (University of Oxford); National Library of Scotland (East Ardsley, Wakefield, United Kingdom : Microform Academic Publishers, 2018)
Sir Charles Vaughan (1774-1849) was a career diplomat who served as British Ambassador to the United States during the period 1825-1835. This collection contains Vaughan's personal and professional papers from before, during, and after his time in Washington. The papers shed light on a number of important subjects and events, from transatlantic trade and the question of the North East boundary to slavery and the experience of Native Americans under the Jackson administration. In addition, the collection includes the papers of one of Vaughan's predecessors, Sir Robert Liston (1742-1836), which provide a unique insight into Anglo-American relations in the late 18th century.
Date range: 1796-1848.
Keywords: Vaughan, Charles Richard, -- 1774-1849 -- Correspondence; Liston, Robert, -- Sir, -- 1742-1836 -- Correspondence; United States -- Foreign relations -- Great Britain; Great Britain -- Foreign relations -- United States